PENGARUH KEGIATAN FUN COOKING TERHADAP KEMAMPUAN GEOMETRI APADA ANAK USIA 4-5 TAHUN DI TK NEGRI PEMBINA KECAMATAN BATANG TUAK INDRAGIRI HILIR - Widya Ningsih; Zulkifli '; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Based on field observations of the child's ability to recognize shapes geometry is low as evidenced by there children who are not able to specify the nature of geometry, sort objects by size and color states. So that should be fun cooking activities. This study aims to determine the effect of cooking fun activities on the ability of the geometry of children aged 4-5 years in kindergarten Negri Pembina District of Batang Tuaka Indragiri Hilir. The sample used in this study 20 0rang. The data collection techniques were used that observation. Data were analyzed using t-test using SPSS 20.0. it can be seen from the analysis of data obtained T_ (table =) 2093 with a 5% error level. Results T_ (count =) 30.098 larger than T_ (table =) ere level of 2093 by 5%. The results of the study nevertheless produce determinant coefficient of (r ^ 2) = 0.51. So that means HA HO rejected and accepted, which means there are significant differences between before and after the experiment through fun cooking activities.Keywords: Ability Geometry, Fun Cooking2